Olympic Britain. Social and economic change since the 1908 and 1948 London Games - Thompson, G.; Hawkins, O.; Dar, A.; Taylor, M.; Battley, N.; Mellows-Facer, A.; Rhodes, C.; Harari, D.; Webb, D.; McGuinness, F.; Berman, G.; Allen, G.; et al. (2011)
Olympics Population Housing & home life Incomes & poverty Leisure & lifestyles London Education Employment The economy Monarchy Technology & communication Transport Parliament & elections Crime & defence